2008
DOI: 10.1115/1.2783849
|View full text |Cite
|
Sign up to set email alerts
|

VIV of a Composite Riser at Moderate Reynolds Number Using CFD

Abstract: The vibratory response of a long slender riser, made of composite materials and subject to an ocean current, is examined for a range of conditions. A major focus of this study is the performance of composite materials when used for risers. The influence of the number of modes of vibration is studied, as is the influence of the mass ratio and the value of the damping coefficient. The flow past the riser is represented by a shear flow, ranging from Re=8000 at the lower end of the riser to Re=10,000 at the upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Another paper presented vortex-induced vibration of composite riser using CFD by T. Rakshit et al [7]. This study has revealed some interesting features regarding VIV of a composite riser.…”
Section: Introductionmentioning
confidence: 76%
“…Another paper presented vortex-induced vibration of composite riser using CFD by T. Rakshit et al [7]. This study has revealed some interesting features regarding VIV of a composite riser.…”
Section: Introductionmentioning
confidence: 76%
“…In addition to studying the mechanical properties of composite materials in sea water, there are effects from fatigue, load distributions, global responses and performances of the full-length composite riser. However, the CPR tube, its stress joint, steel tension joint and other standard joints face global functional and environmental conditions [98,[143][144][145][146]266]. The effects of functional loadings have also been studied in comparative studies presented on both steel and composite risers, including vortex-induced vibrations (VIVs) and resonances on the CPR [11,55,[199][200][201][202]246].…”
Section: Advances In Composite Risersmentioning
confidence: 99%
“…Besides the research of mechanical properties of FRP composite materials in seawater, the responses and performances, including load distributions, fatigue, and vortex-induced vibrations (VIVs) of composite risers under environmental and functional loads have also been investigated [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The improvement of composite risers in performance over a pure metallic mandrel had been proved through a scaled-down test [23].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the VIV of composite risers, it is found that the fundamental frequency of a composite riser with the same boundary condition and geometry was higher than that of a steel riser [18] since the composite riser was much lighter and the value was relatively small [13,14]. The structural damping and tension variations were also significant to the VIV of composite risers [13], i.e., higher tension and damping could reduce VIV-induced fatigue [13,17]. A. F. Omar et al [18] found that the maximum VIV stresses of a composite riser were much smaller than those of a steel riser, indicating the better fatigue lives of composite risers.…”
Section: Introductionmentioning
confidence: 99%